Online-Based Nutrition Education to Reduce Sugar, Salt, and Fat Intake in School Children: A Research Protocol - Mahmudiono, Trias; Indriasari, Rahayu; Pangesututi, Dina Rahayuning; Rachmah, Qonita; Puspikawati, Septa Indra; Wulandari, Fatqiatul; Hidayah, Susi (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Indonesia is currently facing a very complex health problem. Non-communicable diseases (NCDs), for instance, are not only suffered by adolescence or adults, but nowadays, children are also facing the same problem. In children, obesity can be a dangerous risk factor for NCDs later in life. In 2013, the prevalence of overweight and obese children aged 5–12 years in Indonesia reached 18.8%. Meanwhile, in the industrial era 4.0, the development of technology and information is running very rapidly and may affect on food preferences of children, especially sugar, salt, and fat intake on children. Hence, schools play an important role in helping students establish healthy eating behaviors. AIM: Since nutrition was not a curriculum in elementary school Indonesia and studies related to nutrition education with the intensive methods through online platforms are still limited, this study aims to explore the effectiveness of 8-week nutrition education related to improving knowledge, attitude, practice, subjective norms, and perceived behavior control of children toward limiting sugar, salt, and fat intake on children aged 8–12 years. METHODS: This is a randomized control trial study by giving nutrition education intervention related to sugar, salt, and fat consumption to schoolchildren. This study targets elementary schoolchildren using a quasi-experiment design with a pre-post test control group design. The study will be conducted online in 3 urban areas (center) in Indonesia, namely: Surabaya, Semarang, and Makassar City. There are 13 elementary schools involved, consisting of 5 schools from Surabaya City, 4 from Semarang City, and 4 from Makassar City. A total of 300 elementary school students aged 8–12 years as well as 26 teachers are joining in this research. This study has the number: U1111-1268-9302 for the Universal Trial Number and approved by Thai Clinical Trial Registry (TCTR) with identification number: TCTR20210824013.